Bibliometric Analysis of Artificial Intelligent Studies in Education and Pedagogy - Susilowati, Dyah; Saputri, Dian Syafitri Chani; Ria, Reny Refitaningsih Peby; Hidjah, Khasnur (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – Artificial Intelligent (AI) is a technology that is currently developing rapidly. The application of AI in Education (AIEd) is a study that is starting to be of interest to researchers in the field of AI and Education. The purpose of this research is to summarize studies on AIEd from 2018 to 2023 through bibliometric analysis and analyze current study progress, key points, and trends in AIEd related to pedagogy.Method – This research is a bibliometric analysis method. The data were collected from the Scopus database using R Studio software with search keywords of “Artificial Intelligence, Education, and Pedagogy”. A total of 94 articles were reviewed in this study.Findings – The results of the study show that combining the more frequently researched AI and Pedagogy topics with the less researched AIED topics can produce innovative updates and make important contributions in the field of artificial intelligence and education. Research Implications – The impact of this research can open opportunities for researchers to further explore the combination of AIED, AI, and pedagogy topics so as to enrich and expand the scope of research and encourage progress in related disciplines.